KONFLIK BATIN TOKOH UTAMA DALAM NOVEL CINTA DALAM DIAM KARYA SHINEEMINKA - Suldin, Suldin; Syafrial, Syafrial; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study discusses the inner conflict of the main character in the novel Cinta Dalam Diam the paper Shineeminka. This research aims to determine the nature of inner conflict. Research is beneficial in theory, educational and practical. This research is qualitative research types and use of descriptive method. The techniques used in the collection of data on the examination of the technical documentation. Data collected and then analyzed at different stages, namely activities Read repeatedly and minutely in the data, identify identification data and data, and deduce the results of the investigation. Research data comes from the novel Cinta Dalam Diam the paper Shineeminka. From the research that was done, researchers then found 72 inner conflicts of the data of the protagonist. After the data in the analysis there are namely a number of subdivisions of the data, inner conflict 22 id data, the inner conflict of the ego 26 data, and inner conflict superego 24. Most data is thus the data konlik the inner ego. Based on the results of the study it can be concluded that the inner conflict of the main character in the novel Cinta Dalam Diam work of the Shineeminka that dominates the inner conflicts of the ego categoris.Keywords: literature work, literature psychology, internal conflict.